Visual Improvement in Patients With Blunt Traumatic Hyphema After 01 Week - Hafeez, Qamar Zaman; Zafar, Danish; Aqil, Bushra; Khan, Amir Zeb (Biological and Clinical Sciences Research Journal, 2025)
Blunt traumatic hyphema, characterized by hemorrhage in the anterior chamber of the eye due to non-penetrating trauma, is a common ocular emergency with significant implications for visual outcomes. In Pakistan, trauma-related eye injuries are prevalent, particularly among younger males. Early intervention and prompt management play a critical role in visual recovery. Objective: To evaluate the frequency and degree of visual improvement in patients presenting with blunt traumatic hyphema after one week of treatment. Methods: This descriptive observational study was conducted at the Department of Ophthalmology, Ayub Teaching Hospital, Abbottabad, over the period of 3 months from 28 February to 28 May 2025. A total of 161 patients aged 4–40 years presenting within 24 hours of blunt ocular trauma were enrolled using a non-probability consecutive sampling technique. Baseline ophthalmologic examination included visual acuity assessment (Snellen chart), grading of hyphema, intraocular pressure measurement, and dilated fundus examination. Visual improvement was categorized as minimal (20/40–20/30), moderate (20/80–20/40), or significant (20/200–20/50 or better) after one week of follow-up. Data were analyzed using SPSS v20 with chi-square tests applied to determine associations; p<0.05 was considered significant. Results: The mean age of participants was 21.3 ± 8.7 years; 74.5% were male. Most injuries (48.4%) occurred during recreational activities. At baseline, 26.1% had vision 20/200 or worse. After one week, 67.1% of patients showed significant improvement, 19.3% moderate, and 13.6% minimal or no improvement. Grade I hyphema was significantly associated with better visual recovery (p<0.01). Conclusion: A majority of patients with blunt traumatic hyphema showed marked visual improvement within one week of prompt ophthalmic intervention. Early presentation, low-grade hyphema, and immediate care are key factors associated with favorable outcomes. Public awareness, timely medical attention, and targeted preventive measures are essential to reduce the burden of trauma-induced ocular morbidity in Pakistan.